Edukasi Program Guru Penggerak dan Sekolah Penggerak untuk Mewujudkan Tenaga Pendidik dan Sekolah Berkualitas - Gumilar, Gugum; Afriza, Edi Fitriana; Srigustini , Astri; Suherti, Heti; Kurniawan; Widyaningrum, Bakti (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2024)
The Merdeka Curriculum (KM) is a new breakthrough as an effort to create quality education for the Indonesian people. The government strives to have motivating teachers in every educational unit through the teachers as Mobilizers Education (PGP). The drive to become a professional teacher by taking PGP is a requirement for every teacher, however, information related to this program is not yet fully understood. The purpose of this service activity is so that economics subject teachers and schools can find out information related to the Independent Curriculum, economics subject teachers can take part in the Teacher Mobilization program, schools can implement the Independent Curriculum in the school curriculum. The methods used in implementing this service are counseling, lectures, practice and mentoring. Service activities were carried out with a total of 32 lesson hours (JPL) which were held from 10 to 12 August 2023 at the teacher's office at SMA Negeri 1 Parigi, Pangandaran Regency. Community service activities are carried out through counseling, lectures or education, practice and mentoring. The educational activities of the mobilizing teacher program and mobilizing school for economics teachers in Pangandaran Regency are running smoothly. The service implementation process is carried out by following several procedures, namely: 1) teacher counseling or education by teacher assessors from Siliwangi University: 2) tutorials on making learning tools that are in accordance with the Independent Curriculum; 3) participants are asked to practice making learning tools that have been studied previously; and 4) assistance from lecturers to teachers who create learning tools. Even though the service has been running smoothly, further education and training is needed to continue to facilitate the needs of Economic Subject teachers in all sectors.